Conversion model of annual statistics to worst-month statistics of troposcatter - Lei LI; Zhen-wei ZHAO; Zhen-sen WU; Le-ke LIN; Yuan LEI; Rui ZHANG (Tongxin xuebao)
The present worst-month prediction model,however,cannot reflect the me ical characteristics of tro-poscatter propagation accurately.Hence,based on the worst-month prediction models introduced in the recommendation ITU-R P.617-3 and ITU-R P.841-4 respectively,a conversion model of annual statistics to worst-month statistics of tro-poscatter was presented.The corresponding relation between the conversion of annual statistics to worst-month statistics of troposcatter and the refractivity Nsat the earth's surface was derived with the rational n erical calculation and opti-mization method.This model not only solves the disadvantages of the ITU models mentioned above,but also has a better practicability and applicability.Then,using the new model and the trans-horizon propagation loss data banks released by the international telecommunication union(ITU),the worst-month transmission loss for the non-exceedance time percen-tages(50%,90%,99%)of interest are calculated.The prediction results are compared with the recommendation ITU-R P.841 and the trans-horizon propagation loss data banks.The conclusions are helpful for the development and the applica-tion of the troposcatter propagation.